Synthesis and characterization of electrodeposited nanocrystalline ferromagnetic cobalt-iron-platinum alloy films / Teh Seoh Hian - Teh, Seoh Hian (2013)
In this present work, cobalt-iron, cobalt-platinum, iron-platinum and cobalt-iron-platinum systems were synthesized and characterized. Pure Co film was electrodeposited on brass substrates from sulfate plating baths containing sodium saccharin. The compositions of the electrodeposits were found depended on the concentration of Fe in the electrolytic bath. By alloying Co and Fe, binary Co-Fe alloy film was deposited successfully with various composition of Fe in the electrodeposits. Sodium saccharin was added into plating bath as a grain refining agent to improve the quality of the deposits. The crystallite sizes were calculated from the broadening of X-ray diffraction peak and the sizes were in nanoscale. The Co-Fe films with higher Fe content exhibited irregular shaped granules with rougher surfaces. The domain pattern was stripe like for Co and Co94-Fe6 films. The structure was changed to granular domain structures with increasing Fe content. The best soft magnetic properties with high saturation magnetizations and low coercivities were obtained when body-centered cubic (BCC) and face-centered cubic (FCC) phases of Co-Fe system was present. Co-Pt nanocrystalline alloy thin films were electrodeposited using a stable single bath system containing ammonium tartrate solution and ammonia solution as a complex forming additive. Ammonium tartrate was added to promote the polarization of Co2+ and Pt4+ and subsequent enhancement of co-deposition of Co-Pt alloy films. The compositions of the electrodeposits were controlled by adjusting the metal ions in the electrolytic bath and by varying the current density. The as-deposited Co-Pt films contained two possible forms of nanocrystals, which were FCC CoPt3 and face-center tetragonal (FCT) CoPt or amorphous phases. Formation of granules and clusters were observed in all samples. Magnetic Force Microscopy (MFM) characterization of Co43-Pt57 film showed granular domain structure indicating a correlation between magnetic force and surface topography. The saturation magnetization values of as-synthesized nanostructured Co-Pt thin films increased with increase of the Co content. Fe-Pt and Co-Fe-Pt nanocrystalline thin films were electrodeposited on brass substrates from tartrate-alkaline plating bath. The effects of the addition of Co on the properties of Fe-Pt film was focused and investigated. Cobalt was preferentially deposited compared to iron during Co-Fe-Pt film electrodeposition. The microstructure of the films was consisted of spherical granules and clusters. XRD analysis of the films showed the formation of disordered FCC Fe-Pt phase and all peaks were shifted slightly to a higher diffraction angles with increasing cobalt content. The average crystallite size was less than 10 nm. Magnetic properties of the films were increased with the increasing of surface roughness, granule size and clusters. The addition of Co was found to enhance the saturation magnetization and coercivity.